Early detection and primary prevention system in COVID-19 transmission to staff and residents in the department of obstetrics and gynecology - Muhammad Nurhadi Rahman; Detty Siti Nurdiati; Nuring Pangastuti; Anis Widyasari; Fauzan Achmad Maliki; Sarah Ayu Andari; Khairina Hashifah (Journal of Community Empowerment for Health, 2021)
COVID-19 is currently a global pandemic because of its fast transmission in humans. The disease can be symptomatic or asymptomatic. Patients with the disease can transmit the infection to the medical team who are exposed without proper protection. Prevention of transmission is our main focus of attention as well as early recognition of exposed medical teams among obstetrics and gynecology residents and consultants in our hospital. This article aimed to describe the COVID-19 early detection and primary prevention system among staff and residents in the Obstetrics and Gynecology (OBSGYN) Department, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada and Dr. Sardjito General Hospital from April to June 2020. The data were acquired from the reports of the COVID-19 taskforce from the OBSGYN Department. In order to prevent the transmission of COVID-19 infection, actions taken by the OBSGYN Department are as follows: a) arrangement of staff and residents watch schedules, b) usage of PPE (Personal Protective Equipment) according to protocol, c) contact tracing, and d) early detection. Resident watch schedule arrangement is done by withdrawing residents from affiliated hospitals so that the division of daily duty schedules at Dr. Sardjito General Hospital is divided into 2 shifts of 12 hours each. The PPE usage policy is adjusted according to the risk of COVID-19 exposure in different environments and in accordance with established standards. A total of 65 out of 74 residents (88%) had been exposed to suspected COVID-19 cases, and among the exposed residents, 12 residents (18%) were self-isolated because of the occurrence of symptoms, exposure to patients with positive COVID-19 rapid antibody test, or exposure to patients with positive COVID-19 Polymerase Chain Reaction (PCR) test. The department also conducted early detection of COVID-19 infection among all staff members and residents. As many as 13 out of 27 staff (48%) underwent COVID-19 rapid antibody test with 100% negative results, 66 of the 74 residents (89%) also underwent COVID-19 rapid antibody test with 100% negative results. In conclusion, the OBSGYN Department has implemented several measures to prevent transmission of COVID-19 among its staff and residents with adequate satisfactory results.